Directing Urban Planning From the Top: Rezoning the Urban Informal Sector in the Multi-Party System of Yogyakarta City - Achmad Nurmandi (Asia Research Institute, 2011)
Urban management and planning is a political act, most obviously because it involves govermental discretion in the distribution of resources.